$$\newcommand{\id}{\mathrm{id}}$$ $$\newcommand{\Span}{\mathrm{span}}$$ $$\newcommand{\kernel}{\mathrm{null}\,}$$ $$\newcommand{\range}{\mathrm{range}\,}$$ $$\newcommand{\RealPart}{\mathrm{Re}}$$ $$\newcommand{\ImaginaryPart}{\mathrm{Im}}$$ $$\newcommand{\Argument}{\mathrm{Arg}}$$ $$\newcommand{\norm}[1]{\| #1 \|}$$ $$\newcommand{\inner}[2]{\langle #1, #2 \rangle}$$ $$\newcommand{\Span}{\mathrm{span}}$$

# The Product and Quotient Rules

Theorem: The Product Rule

Let f and g be differentiable functions. Then

$\left[f(x) \, g(x)\right] ' = f(x)\, g '(x) + f '(x) \,g(x)$

Proof

We have

Example $$\PageIndex{1}$$:

Find

$dfrac{d}{dx } (2 - x^2)(x^4 - 5)$

Solution:

Here

$f(x) = 2 - x^2$ and

$g(x) = x^4 - 5$

The product rule gives

$dfrac{d}{dx } (2 - x^2)(x^4 - 5) = (2 - x^2)(4x^3) + (-2x)(x^4 - 5)$

### The Quotient Rule

Remember the poem

"lo d hi minus hi d lo square the bottom and away you go"

This poem is the mnemonic for the taking the derivative of a quotient.

Theorem: The Quotient Rule

Let f and g be differentiable functions. Then

$\dfrac{d}{dx} \dfrac{f(x)}{g(x)} = \dfrac{g(x)\, f'(x) - f(x) \, g'(x)}{g(x)^2}$

Example $$\PageIndex{2}$$:

Find y' if $y' =\dfrac{2x - 1}{x + 1}$

Solution: Here

$f(x) = 2x - 1$

and

$g(x) = x + 1$ The quotient rule gives

$\dfrac{ (x + 1)(2) - (2x - 1)(1)}{ (x + 1)2}$

$= \dfrac{2x + 2 - 2x + 1}{(x + 1)2}$

$= \dfrac{3}{ (x + 1)2}$